Implementasi Boundary Element Method untuk Persamaan Panas Syarat Batas Dirichlet-Neumann Domain Lengkungan - Zahroh, Millatuz (Jurnal Matematika; Vol 14 No 2 (2024)DO - 10.24843/JMAT.2024.v14.i02.p180, 2024)
The problem of two dimension heat equation is modeled as Laplace Equation. However, the analytical solution of Laplace Equation is relatively difficult to be solved directly especially with mixed boundary conditions (Dirichlet-Neumann) and arch domain. Then alternatively, numerical method is needed. Boundary Element Method (BEM) is one of powerfull numerical method that can be employed to solve partial differential equations with boundary discretization technique, expecialy for complex domain problem. In this study, two dimensional Laplace Equation with Dirichlet-Neumann boundary conditions and arch domains which is having exact value, is evaluated using Boundary Element Method. The simulation of numerical results obtained with BEM giving indication that this method can produce an accurate numerical solution.